1975
DOI: 10.1152/ajplegacy.1975.228.4.1024
|View full text |Cite
|
Sign up to set email alerts
|

Tissue culture of bone marrow. V. Effect of 5Beta(H) steroids and cyclic AMP on heme synthesis

Abstract: In mice 5beta(H) steroids have been shown tostimulate heme synthesis in vivo. The current studies were undertaken to evaluate the effect of these steroids on heme synthesis by use of the "well" method of marrow culture. The 5beta(H) steroid metabolites 3alpha-hydroxy-5beta-pregnane-11, 20-dione, 3beta-hydroxy-5beta-pregnan-20-one, 3 alpha,17alpha-dihydroxy-5beta-androstan-3-one stimulated Fe uptake by human marrow explants cultured in wells. The dibutyrl analog of adenosine 3',5'-monophosphate (db cAMP) also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…They do not increase the red-cell survival [3], Preliminary studies showed that androgens produced a rise in the serum erythropoietin activity that was attribut ed to the stimulation of endogenous erythropoietin secre tion [1,4], but these data were not confirmed later [5], perhaps because of the low sensitivity of the assay used. Other studies discovered that androgens produced a di rect stimulation of marrow heme synthesis [6], augmenta tion of growth by differentiated stem cells [7] and enhanc ing the sensitivity of erythroid progenitors to circulating erythropoietin [5, 8. 9].…”
Section: Introductionmentioning
confidence: 99%
“…They do not increase the red-cell survival [3], Preliminary studies showed that androgens produced a rise in the serum erythropoietin activity that was attribut ed to the stimulation of endogenous erythropoietin secre tion [1,4], but these data were not confirmed later [5], perhaps because of the low sensitivity of the assay used. Other studies discovered that androgens produced a di rect stimulation of marrow heme synthesis [6], augmenta tion of growth by differentiated stem cells [7] and enhanc ing the sensitivity of erythroid progenitors to circulating erythropoietin [5, 8. 9].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of heme and hemoglobin synthesis by cAMP and dbcAMP in cultures of bone marrow ob tained from various animals was confirmed by inves tigations carried out by many authors [2,14,15,21]. This effect was intensified in the cultures enriched with theophylline [14], Another view on the role of cyclic nucleotides has been presented by Rodgers et al [26].…”
Section: Discussionmentioning
confidence: 84%
“…This effect was intensified in the cultures enriched with theophylline [14], Another view on the role of cyclic nucleotides has been presented by Rodgers et al [26]. This assumes that cGMP is an important nu cleotide mediating the response of erythroid cells to erythropoietin and an active signal in response to erythropoietic stimulating factor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various attempts at verifying the possi bility that Ep action could be mediated through variations of the intracellular level of cyclic nucleotides (a well-established no tion for the action of several proteinaceous hormones [17]) have been reported [5,10,12,18,21]. Increases of cyclic guanosine monophosphate (cGMP) in rabbit bone marrow cultures, in spleen cell suspensions of mice and in fetal liver cells of rats have been found 24 h after treatment with Ep [11].…”
Section: Introductionmentioning
confidence: 99%